Efeitos da terapia de reposição hormonal com estradiol e progestinas sobre o sistema renina-angiostensina vascular de ratas ovariectomizadas - Menezes, Laís Almeida (2018)
Cardiovascular diseases represent the major cause of morbidity and mortality among women of the world and become more prevalent after menopause, which gives the estrogen cardioprotective role. Estrogenic hormone replacement therapy (HRT) alone or in combination with progestins has been the target of studies as an alternative potential in the management of conditions associated with the postmenopausal phase. In this context, medroxyprogesterone acetate (MPA) is the most studied and used progestin in HRT, but its actions on the cardiovascular system have demonstrated antagonistic effects to the benefits of progesterone, and drospirenone (DRSP) exerts a potent antimineralocorticoid action, clinical and experimental evidence of its positive performance. The renin-angiotensin system (RAS) is a key component in the control of cardiovascular homeostasis, which is modulated by the estrogenic condition, and thus, estrogen deficiency modulates this system unfavorably. The vascular effects of estrogen are well elucidated, but there is a shortage of studies investigating the effects of hormonal therapy with MPA and DRSP on the cardiovascular system. Since RAS is an important endocrine axis for the maintenance of cardiovascular hemodynamics and HRT is a therapeutic measure for the damages, symptoms and risks presented at menopause, it is necessary to know the effects of hormonal therapy with these progestins on this system. The experiments were conducted in Wistar sham and ovariectomized rats, which were randomly divided into 5 experimental groups: SHAM, ovariectomized (OVX), OVX treated with 17β-estradiol [E2] (OE2); OVX treated with DRSP and E2 (DRSP + OE2) and OVX treated with MPA (OVX + MPA) orally. After 4 weeks of treatment, vascular reactivity was performed with angiotensin-1-7 (Ang 1-7) dose-response curves, both alone and in the presence of the inhibitors L-NAME, PD123319 and A779.In addition, the aorta was dissected and the protein expression of AT-1, AT-2, MAS, ECA-2 and eNOS were evaluated. There was an increase in body weight of OVX and OVX + MPA animals, the efficacy of ovariectomy was confirmed by the reduction of the uterine weight of OVX rats and the hormone replacement treatments reversed this atrophy. There was an impairment in Ang 1-7-mediated aortic vascular reactivity in OVX rats, being prevented by the therapies, and OE2 rats improved this effect. Vasodilation was abolished in the presence of L-NAME and there was a reduction of the response in the presence of PD123319 in OE2 rats. There was no difference in the protein expression of AT1 and ECA-2 between the groups, Mas expression was higher in the OE2 and DRSP + OE2 and AT2 groups and eNOS was more expressed in OVX + MPA. In view of the abovementioned results, it can be concluded that hypoestrogenism impairs Ang 1-7 induced vasodilatation in vascular reactivity in aortic rings; and the therapies with estradiol and progestins restore these parameters, being this the first time that the effects of the hormonal therapies of MPA and DRSP + E2 on the vascular Ang 1-7 are reported.